SETS-PBL based biology learning: Development of multimedia digital quiz on the cardiovascular system - Nuril Hidayati; Trio Ageng Prayitno (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
There is a need for learning media that integrates learning approaches and models that can help students understand the concepts contextually and empower critical thinking and metacognitive skills. The study aims to produce a multimedia digital quiz on the cardiovascular system material that is valid. The research method uses the Thiagarajan model but only at the define, design, and develop stages. The research objects were three lecturers and 30 students. The research instruments were a needs analysis sheet, a Semester Lecture Plan analysis sheet, a validation sheet from material experts, media experts, practitioners, and a readability test sheet. This research data is in the form of validation scores from experts and readability tests. Research data will be analyzed using quantitative descriptive analysis techniques. The research results show that material experts assessed the multimedia digital quiz at 98.64% (strongly valid), media experts at 97.65% (strongly valid), practitioners at 98.29% (strongly valid), and student readability test results at 87.31% (strongly valid). Furthermore, these findings can be recommended for use by lecturers who teach human anatomy and physiology in universities to empower students' critical and metacognitive thinking skills.Abstrak Perlunya media pembelajaran yang mengintegrasikan pendekatan dan model pembelajaran untuk membantu siswa memahami konsep secara kontekstual serta memberdayakan kemampuan berpikir kritis dan metakognitif. Penelitian bertujuan untuk menghasilkan kuis digital multimedia pada materi sistem kardiovaskular yang valid. Metode penelitian menggunakan model Thiagarajan namun hanya pada tahap define, design, dan develop. Objek penelitian adalah tiga dosen dan 30 mahasiswa. Instrumen penelitian adalah lembar analisis kebutuhan, lembar analisis Rencana Perkuliahan Semester, lembar validasi ahli materi, ahli media, praktisi, dan lembar tes keterbacaan. Data penelitian berupa skor validasi dari para ahli dan tes keterbacaan. Data penelitian akan dianalisis menggunakan teknik analisis deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa ahli materi menilai kuis digital multimedia sebesar 98,64% (sangat valid), ahli media sebesar 97,65% (sangat valid), praktisi sebesar 98,29% (sangat valid), dan hasil tes keterbacaan siswa sebesar 87,31% (sangat valid). Lebih lanjut, temuan ini dapat direkomendasikan untuk digunakan oleh dosen pengajar anatomi dan fisiologi manusia di perguruan tinggi untuk memberdayakan kemampuan berpikir kritis dan metakognitif mahasiswa.